Encapsulating teacher expertise in action. Issue 4 (19th May 2018) - Alterator, Scott; Deed, Craig; Prain, Vaughan
Abstract: Given current extensive expectations of how teachers should excel, any attempt to summarize teacher expertise in action in the second decade of this century may seem at best misguided. However, this has not stopped teacher educators offering diverse metaphoric encapsulations that aim both to distil and prescribe quality teacher practice. In this paper, we attempt to make sense of this diversity, and contribute to a richer dialog about this expertise. We draw on Anna Sfard's influential metaphoric map of competing views of learning as a starting point. We claim that this metaphoric divide is evident in current divergent theories of desirable teaching practices and their metaphoric badging, although there is evidence in current curricular documents of attempts to acknowledge and engage with these accounts. In analyzing these metaphors and their warrants, in a context of intensified accountability, rapid changes to technological affordances, and divided views about how student agency should serve learning processes, we aim to tease out core issues. We draw on recent curricular and policy prescriptions about teacher expertise in the Australian context to illustrate our case. On the basis of our analysis, we propose a bridging metaphor to encapsulate the richness of applied teacher expertise.